(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the central Chubut province, within the Somuncurá-Cañadón Asfalto basin, an outstanding accumulation of vertebrate fossils, including remains of giant titanosaurs, was discovered. Such dinosaur clade constitutes one of the largest found in the world. This contribution provides a preliminary stratigraphic and sedimentological study in order to specify the temporal and stratigraphic position of the vertebrate accumulation, as well as understanding the depositional systems in which the dinosaurs developed. The titanousar remains are contained in the upper section of the Cerro Castaño Member (Cerro Barcino Formation), close to the boundary with the overlying Las Plumas Member. The fossil-bearing rocks are composed of sandstones and tuffaceous sandstones, formerly deposited within floodplains of a volcaniclastic, meandering fluvial system.